2016
DOI: 10.1080/15384047.2016.1264543
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival and complete response rates in patients with advanced melanoma treated with concurrent ipilimumab and radiotherapy versus ipilimumab alone

Abstract: There is a growing body of evidence supporting the synergistic roles of radiotherapy and immunotherapy in the treatment of malignancy. Published case studies of the abscopal effect have been reported with the use of ipilimumab and radiotherapy in metastatic melanoma, but evidence supporting the routine use of this combination of therapy is limited. We conducted a retrospective analysis to evaluate patients treated with ipilimumab for advanced melanoma at a single institution from May 2011 to June 2015. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
106
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(110 citation statements)
references
References 33 publications
2
106
0
2
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][12][13][14][15][16][17][18][19][20][21]28 The few studies that have evaluated the combination of ICIs with RT have shown that these combinations are probably safe for conventional RT and brain stereotactic radiosurgery (SRS). [29][30][31][32][33][34][35][36] Evidence shows that hypofractionated RT (H-RT) is more immunogenic than conventional regimens [37][38][39] and may synergize better with ICIs. However, only a few patients in the reported combination studies received stereotactic ablative body RT (SAbR).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][12][13][14][15][16][17][18][19][20][21]28 The few studies that have evaluated the combination of ICIs with RT have shown that these combinations are probably safe for conventional RT and brain stereotactic radiosurgery (SRS). [29][30][31][32][33][34][35][36] Evidence shows that hypofractionated RT (H-RT) is more immunogenic than conventional regimens [37][38][39] and may synergize better with ICIs. However, only a few patients in the reported combination studies received stereotactic ablative body RT (SAbR).…”
Section: Introductionmentioning
confidence: 99%
“…The finding that the distribution of PD-L1 expression is modified in response to radiation provides a rationale to combine radiation with immunomodulatory drugs, which is currently being evaluated in the clinical setting [16][17][18]. In this regard, in a prospective analysis of melanoma patients treated with CTLA-4 and radiation, a subset of patients benefited from the combinatorial therapy [42]. Furthermore, preclinical studies have indicated that the expression of PD-L1 on the cell surface of tumor cells is altered in response to radiation, thereby potentially contributing to the immunomodulation activity of radiotherapy [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy can liberate and activate CD8+ T cells from an immunosuppressed state, thereby increasing the probability of abscopal effects . Reports of abscopal effects have increased along with the development of combined radiotherapy and immunotherapy, but these have mainly occurred in patients with highly immunogenic melanomas …”
Section: Discussionmentioning
confidence: 99%
“…7,8 Reports of abscopal effects have increased along with the development of combined radiotherapy and immunotherapy, but these have mainly occurred in patients with highly immunogenic melanomas. [9][10][11][12][13] The brain was previously considered an organ with immune privilege because it is difficult for nascent tumorassociated antigens to travel across the blood-brain barrier (BBB). 14 The occurrence of brain metastasis or the administration of radiation treatment often implies BBB opening.…”
Section: Discussionmentioning
confidence: 99%